Promoting mental health equality by investing in organizations: lessons from implementation science. - Stanhope, Victoria; Choy-Brown, Mimi; Doherty, Meredith; Cohen-Serrins, Julian; Baslock, Daniel; Raghavan, Ramesh (Journal of Public Mental Health, 2025)
Purpose: Mental health inequalities based on race and ethnicity in the USA and globally persist despite efforts to address them. The COVID-19 epidemic accentuated these inequalities and demonstrated the extent to which they are linked to social determinants. However, the organizations that are best placed to ameliorate mental health inequalities are often underfunded and under-resourced. Investment strategies that restrict funding for programmatic costs rather than general operating costs often disproportionately impact small organizations that serve communities of color. This study aims to argue that effectively addressing mental health inequalities requires investing in these organizations by applying the lessons learned from implementation science. Findings: This study demonstrates how organizational factors such as leadership, supervision and organizational culture and climate are key to programmatic success and how implementation strategies can target these factors. As promoting health equity is increasingly recognized as a priority outcome for implementation science research, these organizational approaches can inform funders on how to support small organizations that serve marginalized communities, giving them the capacity and flexibility to address mental health inequalities. Originality/value: This paper applies the findings from implementation science to consider how best to support mental health organizations, particularly those well suited to serving the mental health needs of diverse communities.